A ERK/RSK‐mediated negative feedback loop regulates M‐CSF–evoked PI3K/AKT activation in macrophages. Issue 2 (4th January 2018) - Wang, Lijun; Iorio, Caterina; Yan, Kevin; Yang, Howard; Takeshita, Sunao; Kang, Sumin; Neel, Benjamin G.; Yang, Wentian
Abstract : Activation of the RAS/ERK and its downstream signaling components is essential for growth factor–induced cell survival, proliferation, and differentiation. The Src homology‐2 domain containing protein tyrosine phosphatase 2 (SHP2), encoded by protein tyrosine phosphatase, non‐receptor type 11 (Ptpn11), is a positive mediator required for most, if not all, receptor tyrosine kinase–evoked RAS/ERK activation, but differentially regulates the PI3K/AKT signaling cascade in various cellular contexts. The precise mechanisms underlying the differential effects of SHP2 deficiency on the PI3K pathway remain unclear. We found that mice with myelomonocytic cell‐specific [ Tg(LysM‐Cre);Ptpn11 fl/fl mice] Ptpn11 deficiency exhibit mild osteopetrosis. SHP2‐deficient bone marrow macrophages (BMMs) showed decreased proliferation in response to M‐CSF and decreased osteoclast generation. M‐CSF–evoked ERK1/2 activation was decreased, whereas AKT activation was enhanced in SHP2‐deficient BMMs. ERK1/2, via its downstream target RSK2, mediates this negative feedback by negatively regulating phosphorylation of M‐CSF receptor at Tyr721 and, consequently, its binding to p85 subunit of PI3K and PI3K activation. Pharmacologic inhibition of RSK or ERK phenotypically mimics the signaling defects observed in SHP2‐deficient BMMs. Furthermore, this increase in PI3K/AKT activation enables BMM survival in the setting of SHP2 deficiency.—Wang, L., Iorio, C., Yan, K., Yang, H., Takeshita, S., Kang, S., Neel, B.G., Yang, W. An ERK/RSK‐mediated negative feedback loop regulates M‐CSF‐evoked PI3K/AKT activation in macrophages. FASEB J. 32, 875–887 (2018). www.fasebj.org